2019
DOI: 10.2106/jbjs.19.00466
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Spine Surgery Training During Neurological and Orthopaedic Surgery Residency

Abstract: The purpose of this form is to provide readers of your manuscript with information about your other interests that could influence how they receive and understand your work. The form is designed to be completed electronically and stored electronically. It contains programming that allows appropriate data display. Each author should submit a separate form and is responsible for the accuracy and completeness of the submitted information. The form is in six parts. Identifying information. The work under considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…This apprehension is understandable for orthopedic trained surgeons who perform fewer spine procedures in residency compared to their neurological surgeon counterparts. 22 , 23 Moreover, surveyed fellows expect to complete an average of ~240 cases before the end of the academic year, which is less than the 250 cases cited by several authors as the ideal caseload for fellowship. 13 15 Notably, however, only 2 fellowship directors believed that COVID-19 would affect successful fellowship completion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This apprehension is understandable for orthopedic trained surgeons who perform fewer spine procedures in residency compared to their neurological surgeon counterparts. 22 , 23 Moreover, surveyed fellows expect to complete an average of ~240 cases before the end of the academic year, which is less than the 250 cases cited by several authors as the ideal caseload for fellowship. 13 15 Notably, however, only 2 fellowship directors believed that COVID-19 would affect successful fellowship completion.…”
Section: Discussionmentioning
confidence: 94%
“… 27 Graduating orthopedic surgery residents completed an average of 82.8 spine cases during their training, up to 6-times fewer total spine procedures compared with neurosurgery residents. 23 The current crisis highlights a potential fragility of the current spine surgeon training model. Missing 11%–25% of fellowship cases may lead to a substantial reduction in overall spine training before entering practice.…”
Section: Discussionmentioning
confidence: 99%
“…Daniels et al 13 found that neurosurgical residents reported over twice the amount of spine surgery cases than orthopaedic surgery residents from 2009 to 2012 (375 vs. 160, P = 0.002). In a more contemporary analysis, Pham et al 14 reported an over threefold difference in reported spine surgery cases between neurologic and orthopaedic surgery residents from 2009 to 2018 (434 vs. 120, P < 0.01). The results from this study suggest that orthopaedic spine surgeons conduct a comparable total number of spine surgery cases (n = 403) with neurosurgeons at the conclusion of residency (n = 89) and fellowship training (n = 314).…”
Section: Discussionmentioning
confidence: 99%
“…16 Due to the diversity of orthopedic surgeries, the design of robots should consider different demands from surgeons. The common orthopedic surgeries are mainly divided into trauma surgery, 17 spine surgery, 18 and joint surgery. 19 More than that, different types of surgery also correspond to specific surgical operations.…”
Section: Classification Of Surgical Robotsmentioning
confidence: 99%